Verbs : aspect and causal structure - Croft, William, 1956- (Oxford linguistics., 2012)
This book presents a model of event structure for the analysis of aspectual constructions and argument structure constructions in English and other languages. Representing the culmination of two decades of the author's research and thought, it explores the contribution of semantics to the argument-structure and tense-aspect constructions in which verbs occur, integrating the aspectual and causal structures of events. The argument is framed in relation to current and previous scholarship and takes full account of diachronic and usage-based research. Professor Croft's analysis encompasses the full range of English verb classes and is enriched throughout by a strong typological dimension. The syntax and semantics of verbs are always seen from a crosslinguistic perspective. This allows the author to demonstrate the generality of his theory and to show how it breaks new ground in predicting and explaining linguistic facts. The subject of the book is at the heart of current work in syntax and semantics and the interface between them. It will interest semanticists, syntacticians and cognitive and functional-typological linguists. The transparency of the author's style and his avoidance of theory-dependent constructs will extend its appeal to linguists of all theoretical stripes.